Evaluating Executive Functions in Patients with Juvenile Myoclonic Epilepsy Using Frontal Assessment Battery - Hossein Sanjari Moghaddam; Masoud Doost Hoseini; Mohammad Reza Khaleghi; Abbas Tafakhori; Mahsa Dolatshahi; Shayan Pourmirbabaei; Elmira Agah; Shakila Meshkat; Vajiheh Aghamollaii (Behavioural Neurology)
Objective. In this study, we aimed to evaluate the executive profile of juvenile myoclonic epilepsy (JME) patients using the Frontal Assessment Battery (FAB) as a bedside screening tool and investigate its association with seizure proximity, family history of epilepsy, and polytherapy/monotherapy with antiepileptic drugs (AEDs). Background. JME patients have deficits in various aspects of executive functions. FAB has proved to be a useful tool for evaluating executive functions in clinical settings. Methods. Thirty-one JME patients and 110 healthy controls (HCs) were enrolled in this study. The participants were assessed using six subsets of FAB, including conceptualization, mental flexibility, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy. Results. Compared to HCs, JME patients showed lower scores in conceptualization, mental flexibility, programming, sensitivity to interference, and total FAB. The number of AEDs (polytherapy versus monotherapy) and duration of time since the last seizure had no significant effect on FAB scores in JME patients. We found significant associations between disease duration and conceptualization, mental flexibility, inhibitory control, and total FAB score only in JME patients with recent seizure. Finally, receiver operating characteristic (ROC) analysis showed area under the curve (AUC) of 0.971 (95% confidence interval (CI): 0.947–0.994) for FAB total score, 0.933 for conceptualization (95% CI: 0.973-894), and 0.836 for mental flexibility (95% CI: 0.921-751). Conclusions. In summary, JME patients had deficits in different aspects of executive functions. FAB is a useful clinical tool for evaluation of executive functions in JME patients.